2013
DOI: 10.5262/tndt.2013.1002.07
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalance of the Hepatitis B and C in Patients with Chronic Kidney Disease without History of Renal Replacement Therapy

Abstract: OBJECTIVE: Hepatitis B (HBV) and hepatitis C (HCV) viruses are signifi cant causes of morbidity and mortality in patients with chronic kidney disease (CKD). There is insuffi cient data on seroprevalence of HBV and HCV in CKD patients without renal replacement therapy (RRT). MATERIAL and METHODS:Patients diagnosed as having CKD without RRT were analyzed. Seven hundred and eighty cases included study. RESULTS:The seroprevalence of HbsAg and Anti-HCV were 3.5% and 1.3%, respectively. The seroprevalence of Anti-HB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
2
0
2
Order By: Relevance
“…The majority (≥ 60%) of CKD patients acquiring chronic HBV infection are known to become chronic carriers because of a deficiency in CD8+ cytotoxic and CD4+ helper T lymphocytes[ 1 , 11 ]; however, the incidence was unknown. Only two hospital-based studies and one community-based study reported that the prevalence of HBV infection was 10.5% in Turkish patients with CKD stages 4-5[ 26 ], 3.5% in Turkish patients with CKD stages 3-5[ 10 ], and 9.9% in Taiwanese patients with CKD stages 1-5[ 27 ]. Only two case-series studies and one population-based study from China reported the potential risk of ESRD in target CKD subpopulations such as patients with primary GN[ 28 ] or HBV-GN[ 8 ], and those with diabetic nephropathy[ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority (≥ 60%) of CKD patients acquiring chronic HBV infection are known to become chronic carriers because of a deficiency in CD8+ cytotoxic and CD4+ helper T lymphocytes[ 1 , 11 ]; however, the incidence was unknown. Only two hospital-based studies and one community-based study reported that the prevalence of HBV infection was 10.5% in Turkish patients with CKD stages 4-5[ 26 ], 3.5% in Turkish patients with CKD stages 3-5[ 10 ], and 9.9% in Taiwanese patients with CKD stages 1-5[ 27 ]. Only two case-series studies and one population-based study from China reported the potential risk of ESRD in target CKD subpopulations such as patients with primary GN[ 28 ] or HBV-GN[ 8 ], and those with diabetic nephropathy[ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chronic HBV infection has also been shown to progress to ESRD in special populations with diabetic nephropathy[ 7 ] and HBV-related glomerulonephritis (HBV-GN)[ 8 ]. CKD patients were reported to be at increased risk of acquiring HBV infection[ 1 , 9 , 10 ], more vulnerable to the cytopathic effects of HBV infection, and prone to becoming chronic carriers. This could be because of increased exposure of these patients to blood products, and the immunosuppressive effects of CKD[ 1 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…HD hastaları arasında dünyada yapılan çalışmalar incelendiğinde, anti-HCV pozitifliğinde zaman içinde düşüş gözlendiği gibi bazı ülkelerde ise artışlar saptanmıştır. Yani problem hala devam etmektedir (2,(16)(17)(18). Diyaliz hastalarında HCV enfeksiyonunun ayrı bir önemi vardır, çünkü nozokomiyal geçiş nedeniyle normal topluma göre görülme sıklığı çok daha yüksektir (19,20).…”
Section: Bulgularunclassified
“…Farklı ülkelerde yapılan çalışmalarda anti-HCV pozitiflik oranının coğrafi bölgeler arasında %4 ile %59 arasında değiştiği bildirilmiştir (17,20,(22)(23)(24)(25)(26). Asya-Pasifik ülkelerinde diyaliz hastalarında HCV seroprevalansı %0.7-%18,1 arasında bildirilmiştir (27) (16). Farklı çalışmalarda birçok araştırmacı cinsiyete göre dağılımda bir farklılığın olmadığını belirtmişlerse de, bazı araştırmacılar saptadığımız sonuçlara benzer şekilde HCV enfeksiyonunun cinsiyete göre dağılımda farklılıklar gösterdiğini belirtmişlerdir (19,22,25).…”
Section: Bulgularunclassified